Multi-Modality at Tourism Destination: An Overview of the Transportation Network at The UNESCO Heritage Site Melaka, Malaysia - Ahmad Sahir Jais; Azizan Marzuki (International Journal of Supply Chain Management, 2019)
Antecedents of a tourism destination’s sustainability and competitiveness rely on its transportation networks to facilitate the movement of traffic for locals and tourist alike. Multi-modality is vital to support the local economies, which garner its revenue from tourism activities. Modality plays a vital role to facilitate the mobility of tourists, inter destinations and within the destinations and relates to the accessibility aspects at a tourism destination. An observational study, paired with a comprehensive analysis of literature, is conducted to explore the gamut of the transportation networks in Melaka and its relation and contribution to the tourism industry. The investigation shows that the Melaka’s tourism industry is dependent on the transportation networks. Public transportations are found to be inadequate. Issues such as seasonal congestion and public transportation inadequacy need to be addressed immediately to ensure that smooth flow and dispersal of traffic, entering and exiting Melaka.